Normal Coordinate Analysis of Polyvinyl Acetate - Rosemal H. Mas Haris, Mas; Kathiresan, S.; Mohan, S. (Asian Journal of Chemistry, 2010)
Fourier transform infrared (FT-IR) and FT-Raman spectra of polyvinyl acetate have been recorded in the range of 4000- 400 and 4000-100 cm-1, respectively. In the present investigation, a detailed assignment of the observed fundamental bands of polyvinyl acetate has been analyzed in terms of peak position and relative intensities. With the hope of providing more and effective information on the fundamental vibrations, a normal coordinate analysis has been performed on polyvinyl acetate by assuming Cs symmetry. The simple general valance force field (SGVFF) method has been employed in normal coordinate analysis. The potential energy distribution for each fundamental vibration has also been calculated. The potential energy distribution contribution corresponding to each of the observed frequencies shows the reliability and accuracy of spectral analysis.